The effects of varied coconut methyl ester biodiesel/diesel blend ratios on the performance and NOx emissions of a multi-cylinder common rail diesel engine - Reyes, Joseph Gerard T. (College of Engineering, University of the Philippines Diliman, 2015)
The Philippine Biofuels Act of 2006 (RA 9367) mandates the use of fuels obtained from biological sources in the country in order to reduce dependence on imported petroleum. One of the primary local sources for these fuels is coconut oil, from which coconut methyl ester (CoME) biodiesel is produced. The act states the amount of biodiesel blended into petroleum-based diesel will increase upon implementation of the act. One of the issues concerning the use of biodiesels in general is the production of nitric oxide (NOx), a regulated exhaust emission stated in the Philippine Clean Air Act of 1999 (RA 8749). With the upcoming implementation of more stringent emission standards by RA 8749, in-depth studies on the increase in blend ratios of CoME/neat diesel and their effects on diesel engine performance and emissions were deemed necessary in order to establish a view of the effectiveness of both policies in the Philippine setting. CoME/neat diesel blends of 2, 5, 10, 15 and 20%, by volume, were tested using a stock common-rail direct ignition (CRDI) engine in a test bench and subjected to 100% and 50% load conditions at test speeds of 800,1200,1600, 2000,2400,2800, 3200, 3600 and 4000 rpm. Engine performance parameters such as torque, brake power, fuel flow rates and brake specific fuel consumption were measured and determined. NOx levels, alongside those of other emissions, were measured and analyzed using measured and calculated parameters such as fuel injection timing, fuel injection pressures, injection durations, and net heat release rates. The engine performance, based on engine torque, power, fuel flow and brake specific fuel consumption, was observed to be identical for all fuels in the 800 to 2400 rpm range and diverged at the higher speeds. On the other hand, test results showed that all the biodiesel blends produced up to 29% more NO, than neat diesel for all engine loads and speeds, despite the sustained injection timings and injection pressures managed by the engine's electronic control unit. These results could be attributed to the physical properties, such as the densities, viscosities, speed of sound and bulk moduli, of the biodiesel blends and the corresponding response of the fuel injection system during fuel spray and the engine used in the tests.